PEMANFAATAN SOFTWARE MAESTRO SEBAGAI MEDIA PEMBELAJARAN NOTASI BALOK PADA KELAS VIII DI MTS ISLAMIYAH ULU DANAU - Zuhdi, Hamzir; Adoma, Auzy Madona (Besaung : Jurnal Seni Desain dan Budaya, 2022)
The formulation of the problem in this study is how to use Maestro software as a learning medium for beam notation in class VIII at MTs Islamiyah Ulu Danau? The purpose of the study was to find out how to use maestro software in the learning process of beam notation at MTs Islamiyah Ulu Danau. The method used in this research is a qualitative approach. The data collection technique used is triangulation, namely observation, interviews, and documentation. Based on the results of the study, it was found that the use of maestro software really helped students and teachers in carrying out the teaching and learning process, with the maestro students became easier to understand and more active in learning, the easy use of maestro also helped students to quickly understand and run the application before being notified by the teacher. he importance of empowering technology in education is to support easy and fun learning. To achieve the goals of education, aspects that support the learning process are also needed, including teachers, active students, innovative media and the availability of qualified facilities and infrastructure. The maestro software itself is a technological music published by Future Sculptor for Android users, this software serves to make it easier for users to write block notation. In addition to writing block notation, we can also hear the notes we make on our worksheets, making it easier to correct if there is an error in the position of the typed note. Utilization of maestro software at MTs Islamiyah Ulu Danau here is used as a notation writing medium where students will later copy the notation of the national anthem.